If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 2 + 6 = 7 Reorder the terms: 2 + 6 + b = 7 Combine like terms: 2 + 6 = 8 8 + b = 7 Solving 8 + b = 7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + b = 7 + -8 Combine like terms: 8 + -8 = 0 0 + b = 7 + -8 b = 7 + -8 Combine like terms: 7 + -8 = -1 b = -1 Simplifying b = -1
| (-1)x(-3)= | | 4a+2s=588 | | -6-5x=-26 | | 15z-12z-2z=15 | | 3(6e-4)=e+4 | | 7(x+2)-5=7x+9 | | 4(10x-8)=x+9 | | 18y+y-14y-2y+2y=15 | | 5x+7x+14=31 | | X+9=-x+11 | | x=4y+10 | | 0+0.99X=10+0.89X | | (x-6)(x+11)=0 | | 460+x=x | | 10(9k-1)=k+9 | | -8j+4j=12 | | (x+5)(x+5)(3x-5)=0 | | 4x^2-32x-8=0 | | 4x-15+15x+5=180 | | 2y+8=22y | | 14n-2n+n-12n=11 | | 24-7m=10 | | (-5)x(5)= | | y=-3(6)+5 | | 9x-10+2x-3=42 | | 3/5k+5=17 | | 2q+10=6 | | -11(2m-6)=3m+9(3m-10) | | 10h=s | | 3h+c+2h+3c= | | 7=-6m+5 | | -6-2(9x-2)=-5 |